2009
DOI: 10.2984/049.063.0406
|View full text |Cite
|
Sign up to set email alerts
|

Historical Ecology in Kiribati: Linking Past with Present

Abstract: Compared with ''high'' islands, atolls and table reefs have received little attention from archaeologists focusing on historical ecology in Oceania. Limited archaeological investigations in the three archipelagoes composing the Republic of Kiribati (Gilbert, Phoenix, and Line Groups) reflect primarily culture historical reconstructions. Given the unique environmental challenges posed by coral islands, their potential for prehistoric ecological research should be recognized. By contrast, the last 50 years have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 95 publications
0
19
0
Order By: Relevance
“…In the Pacific, some of the gaps in our knowledge of small island colonization and adaptations have been filled by work on atolls or small limestone islands in Micronesia, including the Marshall Islands (e.g., Weisler 2001aWeisler , 2001bWeisler , 2002Weisler et al 2012;Yamaguchi et al 2009), Mwoakilloa (Poteate et al 2016), Fais (Intoh 2008;Intoh and Shigehara 2004), Kiribati (e.g., Thomas 2007aThomas , 2007bThomas , 2009Thomas , 2014, and Palau (e.g., Clark 2005;Clark et al 2006;Fitzpatrick 2003;Fitzpatrick et al 2011). There are also many other similar ones in Polynesia such as the Cook Islands (e.g., Allen and Craig 2009; Allen and Steadman 1990; Allen and Wallace 2007; Kirch et al 1995), the Tuamotu archipelago (e.g., Conte and Dennison 1995), the remote islands of Henderson, Pitcairn (Weisler 1995), and Rapa Nui (e.g., Hunt and Lipo 2011), and even the Arawe Islands of Papua New Guinea (Specht et al 2016), all of which have enhanced our understanding of small island adaptations.…”
Section: The Pacificmentioning
confidence: 99%
“…In the Pacific, some of the gaps in our knowledge of small island colonization and adaptations have been filled by work on atolls or small limestone islands in Micronesia, including the Marshall Islands (e.g., Weisler 2001aWeisler , 2001bWeisler , 2002Weisler et al 2012;Yamaguchi et al 2009), Mwoakilloa (Poteate et al 2016), Fais (Intoh 2008;Intoh and Shigehara 2004), Kiribati (e.g., Thomas 2007aThomas , 2007bThomas , 2009Thomas , 2014, and Palau (e.g., Clark 2005;Clark et al 2006;Fitzpatrick 2003;Fitzpatrick et al 2011). There are also many other similar ones in Polynesia such as the Cook Islands (e.g., Allen and Craig 2009; Allen and Steadman 1990; Allen and Wallace 2007; Kirch et al 1995), the Tuamotu archipelago (e.g., Conte and Dennison 1995), the remote islands of Henderson, Pitcairn (Weisler 1995), and Rapa Nui (e.g., Hunt and Lipo 2011), and even the Arawe Islands of Papua New Guinea (Specht et al 2016), all of which have enhanced our understanding of small island adaptations.…”
Section: The Pacificmentioning
confidence: 99%
“…stone, clay, freshwater, terrestrial animals), susceptibility to and lack of ability to respond to natural catastrophes, and the general marginality of these environments. However, archaeologists are becoming increasingly aware that despite their small size—and what many would consider impoverished terrestrial environments—people nonetheless appear to have begun occupying (at least intermittently) atolls almost immediately after sea levels had stabilized (Riley 1987; Shun and Athens 1990; Weisler 1999a, 2001a, 2001b; Dickinson 2003, 2004, 2009; Thomas 2009; Weisler et al 2012) and did so successfully and continuously for two millennia through a variety of sociocultural changes and technological innovations, such as accessing freshwater by digging wells to tap the Ghyben-Herzberg lens.…”
Section: Introductionmentioning
confidence: 99%
“…They may have also provided the opportunity to develop independent modes of settlement and sociopolitical institutions. The rich and abundant resources of the coral reef, would have also proved quite attractive to atoll colonizers, who benefited from the high ratio of reef to terrestrial land area (Weisler 2002;Thomas 2009). As people familiar with long-distance oceanic travel, it is unlikely that Pacific Islanders of Chronological Sequence for Pingelap Atoll 773 the past conceived of habitable space as being delimited by the shoreline (e.g., Hau'ofa 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Project personnel determined the locations of test units based on the intention to construct a preliminary settlement history for Pingelap and to examine land use practices ( Figure 3). Following procedures from previous atoll studies (e.g., Thompson 2010;Poteate et al 2016), which have indicated that points of high elevation on atolls are likely to represent long-term settlement and that central areas have the longest occupation because of a larger freshwater lens (e.g., Riley 1987;Best 1988;Weisler 1999a;Yamaguchi et al 2005;Thomas 2009;Figure 3 Test unit and shovel test locations. Drafted by Joel Butler.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation